SISTEM ENKRIPSI DAN DEKRIPSI SERTA PENYEMBUNYIAN FILE TEKS MENGGUNAKAN ALGORITMA RC4 DAN END OF FILE (EOF) PADA CITRA DIGITAL - Damanik, Romanus (Journal Information System Development (ISD), 2018)
Basically, confidential data needs to be stored or delivered in a certain way so as not to be known by unauthorized foreign parties. And to overcome the problem then created the science of cryptography and steganography. One example of a cryptographic algorithm is the Rivest Code 4 (RC4) algorithm, and one example of the steganographic algorithm is End Of File (EOF). Cryptographic algorithms can be combined with steganographic algorithms so that the secret messages we have are more secure than foreign interference. First of all secret messages that we have first encrypted using the Rivest Code 4 (RC4) algorithm, then the encrypted ciphertext is hidden / inserted in the image / image media with the End Of File (EOF) steganography method.Keyword: Kriptografi, steganografi, rivest code 4, end of file, cipherteks